OPTIMALISASI PEMANFAATAN LAHAN UNTUK PENGEMBANGAN KOMODITI KAKAO (Theobroma cacao L.) DI KECAMATAN TOMPOBULU KABUPATEN BANTAENG - Fadhil Surur (Teknosains, 2017)
Agriculture, forestry and fisheries became the most impact sectors of the regional economy contributed 32.12%. Tompobulu Distrct is one of the districts as a center for the development of cocoa in Bantaeng Regency. Spatial Policy Bantaeng to assigned Tompobulu as an area of agriculture development. The general objective of this study identifying the level of development of cocoa, identifying the level of suitability of land for the development of cocoa, determining regional growth centers, determine the location of cocoa agro-industry development and direction of laud optimization for the development of cocoa in the District Tompobulu. Components of the data in this study a quantitative and qualitative data. The analytical method used is the analysis of the base area, land suitability analysis, schallogram analysis and analytical determination of agroindustrial region. Based on the analysis commodity, obtained Village Lembang Gantarang Keke, Patalassang, Bonto-bontoa, Banyorang, and Campaga as a central commodity of cocoa. The level of suitability of land for cocoa more dominant on land suitability classes S1, which reached 55.71%, while the suitability S2 class range of 4.11%, in conformity N class is quite high, at 39.59%. Service centre refers to Banyuorang as the primary that will serve the other area. Results of the analysis showed the most ideal ndustrial location is Gantarang Keke. Direction to land use optimization is to maximize land use S3 and N for non-agricultural activities, protect the land land with a value of S1 and S2, protected areas, reduce farming activities and to developing the socio-economic facilities on unproductive land.